COMPUTERIZED SYSTEM OF CASH FLOWS IN AND OUT OF THE KELURAHAN CANDI SEMARANG OFFICE - Devi Ayu Indriyani; Indra Ava Adianta (Lembaga Pengembangan Kinerja Dosen, 2021)
Cash flow statement is a report on cash receipts and disbursements for a period. Useful for helping employees to assess the amount and uncertainty of future cash flows. Because cash plays an important role in carrying out office operational activities both now and in the future, therefore the office must be able to control the use of cash to ensure that office operations continue to run well. Likewise, the purpose of the research entitled